2017
DOI: 10.1111/andr.12435
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between testosterone in serum, saliva and urine during treatment with intramuscular testosterone undecanoate in gender dysphoria and male hypogonadism

Abstract: Long-term testosterone replacement therapy is mainly monitored by trough levels of serum testosterone (S-T), while urinary testosterone (U-T) is used by forensic toxicology to evaluate testosterone doping. Testosterone in saliva (Sal-T) may provide additional information and simplify the sample collection. We aimed to investigate the relationships between testosterone measured in saliva, serum and urine during standard treatment with 1,000 mg testosterone undecanoate (TU) every 12th week during 1 year. This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Given the extreme but transient elevations of serum T concentration in otherwise healthy young females are not consistent with any known physiological, pharmacological, or pathological conditions, it is highly likely that these findings are due to administration of exogenous T. Previous reports have investigated serum T measurement by LC–MS to detect exogenous T in experimental studies of men administered one or multiple doses of testosterone gel or testosterone ester injections . However, there is only a single study in women .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extreme but transient elevations of serum T concentration in otherwise healthy young females are not consistent with any known physiological, pharmacological, or pathological conditions, it is highly likely that these findings are due to administration of exogenous T. Previous reports have investigated serum T measurement by LC–MS to detect exogenous T in experimental studies of men administered one or multiple doses of testosterone gel or testosterone ester injections . However, there is only a single study in women .…”
Section: Discussionmentioning
confidence: 99%
“…Given the extreme but transient elevations of serum T concentration in otherwise healthy young females are not consistent with any known physiological, pharmacological, or pathological conditions, it is highly likely that these findings are due to administration of exogenous T. Previous reports have investigated serum T measurement by LC-MS to detect exogenous T in experimental studies of men administered one or multiple doses of testosterone gel 13,[21][22][23][24][25] or testosterone ester injections. [26][27][28] However, there is only a single study in women. 29 In that study, ten Japanese women (six with homozygous and three with heterozygous UGT2B17 deletion genotype) administered a single intramuscular injection of 100 mg T enanthate mostly displayed small increases (not exceeding 1.5) of urine T/E ratio.…”
Section: Athlete Amentioning
confidence: 99%
“…These binding proteins can act as a reservoir for the steroid and protect it against extensive metabolism of active (free) steroids during passage of the blood through the liver [58]. Recently, salivary and serum testosterone levels were found to correlate significantly with calculated free testosterone in both controls and patients, whereas salivary and urine testosterone showed weaker correlations [59]. Other researchers reported that the correlation of serum and salivary concentrations taken before and after exercise was not as consistent as that observed during rest [60].…”
Section: Discussionmentioning
confidence: 99%
“…To increase compliance and reduce the demands on participants, hormonal concentrations were evaluated via fasting salivary collections rather than in serum. It has been confirmed in several studies that salivary measurements of testosterone, DHEA-S, cortisol, and estradiol correlate well with serum levels (Arregger, Contreras, Tumilasci, Aquilano, & Cardoso, 2007;Francavilla et al, 2018;Lood et al, 2018). However, their accuracy as an outcome measure can be compromised by their rapid diurnal variability (Wood, 2009).…”
Section: Study Limitations and Directions For Future Researchmentioning
confidence: 86%